Peripheral endothelial dysfunction as a marker of cardiovascular risk in physically healthy patients with schizophrenia and related psychoses: a matched case control study - Protopopova, Dita; Masopust, Jiri; Malý, Radovan; Valis, Martin; Dostalova, Gabriela; Ranna, Kristina; Bažant, Jan (Neuro endocrinology letters, 2014)
OBJECTIVES: Our aim was to assess endothelial function in physically healthy patients with schizophrenia and related psychoses and to compare the results with healthy controls. Endothelial dysfunction was shown to predict future cardiovascular events in general population so we assumed to find a higher prevalence of endothelial dysfunction in patients with psychosis, as their cardiovascular morbidity is markedly higher than in general population, and to confirm the referred correlation with the traditional cardiovascular (CV) risk factors. DESIGN: We assessed the traditional CV risk factors and endothelial function using non-invasive peripheral arterial tonometry (EndoPAT2000) in 50 stabilized and medicated schizophrenic patients (aged between 18 and 50 years) without any history of cardiovascular diseases and compared the results with 50 age-matched healthy controls. SETTING: Psychiatric Clinic, University Hospital, Hradec Kralove and 2nd Department of Internal Medicine, General University Hospital, Prague, Czech Republic RESULTS: There was no difference in relative hyperaemia index as an endothelial function measure between patients and controls (2.19±0.68 vs. 1.98±0.57, p=NS) and there were also no correlations between reactive hyperaemia index and the traditional CV risk factors, illness duration or psychotic symptoms. On the other hand, the two study groups differed significantly in almost all traditional CV risk factors.
Keywords: dospělí; Female; Prevalence; biologické markery; Endothelium, Vascular; Biomarkers; Adult; mladý dospělý; ženské pohlaví; Predictive Value of Tests; Adolescent; prediktivní hodnota testů; lidé; psychotické poruchy; studie případů a kontrol; schizofrenie; Risk Factors; prevalence; Male; Cardiovascular Diseases; Case-Control Studies; Young Adult; Psychotic Disorders; Schizophrenia; rizikové faktory; kardiovaskulární nemoci; cévní endotel; lidé středního věku; mužské pohlaví; Middle Aged; mladiství; Humans